ВИХОВАННЯ МУЗИЧНОЇ КУЛЬТУРИ УЧНІВ в КОНТЕКСТІ ГУМАНІСТИЧНОЇ ПЕДАГОГІКИ (Педагогіка вищої та середньої школи, 2007)
Modern approaches to the aims of musical education that are conceptually important in terms of humanistically oriented pedagogics are regarded in the article.